Mini-Review: Nod Factor Regulation of Phytohormone Signaling and Homeostasis During Rhizobia-Legume Symbiosis - Buhian, William P.; Bensmihen, Sandra (Frontiers in Plant Science, 2018)
The legume-rhizobia symbiotic interaction is a mutualistic association leading to intra-cellular accommodation of bacteria by the plant, whereby bacteria provide plants with nitrogen compounds and the plant provides bacteria with carbon sources. This interaction is costly for the plant that tightly controls its establishment and functioning.This tight interaction largely relies on a molecular dialog between the plant and the bacteria involving rhizobial lipo-chitooligosaccharide signals called Nod Factors (NF). Specific NF perception is generally required for rhizobia to enter root cells through newly formed intracellular structures called infection threads. Concomitantly to infection thread formation in root hairs, root cortical cells start to divide to create a new root organ called the nodule, which will provide the bacteria with a specific micro-environment required for symbiotic nitrogen fixation. During all these steps of plant-bacteria interaction, new plant cellular compartments and developmental programs are activated. Phytohormones are potent regulators of plant cellular and developmental plasticity, as well as influential endogenous signals that rapidly control plant responses. Although early symbiotic responses were known for decades to be linked to phytohormone-related responses, new data was recently gained on the molecular mechanisms involved and their link with the control of early symbiotic signaling. Reciprocally, NF signaling was also shown to target phytohormone signaling pathways. In this review, we will focus on the emerging notion of NF and phytohormone signaling crosstalk, and how it could contribute to the tight control of early bacterial accommodation by legume plants.